A Robotic Microforceps for Retinal Microsurgery With Adaptive Clamping Method - Zhang, He; Yi, Haoran; Wang, Chunbo; Yang, Jiahui; Jin, Taixian; Zhao, Jie (IEEE/ASME transactions on mechatronics, 2024)
Epiretinal membrane peel surgery requires the surgeon to perform precise operation on delicate tissue within the narrow space of the eye, which is considered as one of the most technically demanding procedures. Using surgical robots to assist surgeons in performing operations is a recognized development direction. The automatic microforceps, as a device mounted at the end of the robotic arm and directly in contact with the affected area, has been the subject of research by many scholars. However, current research has significant shortcomings in both the calibration algorithms for the sensors and the control methods for the microforceps. In this article, we introduce an automated microforceps designed for epiretinal membrane peeling procedures. Despite its compact radial dimension of just 20 mm, the jaw of the microforceps possesses the following two degrees of freedom (DOF): 1) rotation and 2) closure. Subsequently, we analyzed the changes in the physical model of the 3-DOF force sensor after its integration into the microforceps, leading us to propose a refined calibration algorithm tailored for our designed automated microforceps. Furthermore, we introduced a force-based adaptive clamping method suitable for variety of unknown thickness films. Both polyethylene terephthalate (PET) film experiments and generalization experiments demonstrated the stability and generalizability of the adaptive clamping method.